PENGARUH PENERAPAN SALURAN DISTRIBUSI TERHADAP TINGKAT PENDAPATAN PADA PENGUSAHA KRIPIK PISANG DIKOTA METRO TAHUN 2016 - Tri Aryanti Tri Aryanti; Maryatun Maryatun (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2017)
Marketing is an essential activity in the company. Marketing is a system in the whole of the business activities shown to plan, price, promote, and distribute goods and services that satisfy the needs, both of the existing buyers and the potential buyers. The purpose of this research is: "to know the effect of distribution line towards income level of banana chips entrepreneurat Metro City in 2016". While the hypothesis in this study is: "There is a positive influence of the application of distribution line towards income level of banana chips entrepreneurat Metro City in 2016". Calculation analysis of t_count and t_tabel above mentioned means that t_count> t_table. And t_tables can be viewed in the G list. At a significant level of 5% ie 35.9> 1.73 and a significant level of 1% that is 35.9> 2.55. Thus the hypothesis reads "there is a positive influence of the effect of distribution line towards income level of banana chips entrepreneurat Metro City in 2016". Keywords: Distribution line, Income level.